Autologous platelet lysate local injections for the treatment of refractory lateral epicondylitis - Tan, Xun-xiang (J Orthop Surg Res, 2016)
BACKGROUND: The purpose of this study was to investigate the efficacy and safety of autologous platelet lysate (APL) local injections in reducing pain and improving function in patients with refractory lateral epicondylitis. METHODS: A total of 56 patients with refractory lateral epicondylitis were enrolled in this study. All the patients received three injections in one course of treatment. Subjective assessments include visual analog scale (VAS) pain score and Mayo elbow score before injection (baseline) and at 1, 6, and 12 months after injection. RESULTS: Significant differences were observed in VAS and Mayo scores at baseline and at 1, 6, and 12 months after injection. Overall, the injections of APL improved local symptoms and all the patients recovered to normal elbow function with 12 months follow-up. CONCLUSIONS: Local injections of APL resulted in favorable clinical outcomes for the treatment of lateral epicondylitis. APL could be clinically effective in the treatment of lateral epicondylitis.